The dominance of Kenyans in distance running - Pitsiladis, Y. P.; Onywera, V. O.; Geogiades, E.; O'Connell, W.; Boit, M. K. (Equine and Comparative Exercise Physiology, 2004)
Kenyan runners, and especially those originating from the Kalenjin tribe, have dominated international middle- and long-distance running for over 40 years, prompting significant interest in the factors contributing to their success. Proposed explanations have included environmental factors, psychological advantage and favourable physiological characteristics, which may be genetically conferred or environmentally determined. Running is inherent within local Kenyan tradition and culture, and the Kenyan way of life, which involves many outdoor activities and pastimes in addition to mostly unfavourable living conditions, is conducive to enhanced distance running performance. Despite economic deprivation, Kenya has produced world and international running champions repeatedly over the past few decades; these champions have become role models for the younger generations, who take up running in the hope of a better future for themselves. Favourable environmental conditions such as altitude, diet and anthropometry, in addition to the motivational and socio-economic factors mentioned above, have all been proposed as possible reasons for the unsurpassed achievements of Kenyan distance runners. However, the fact that the majority of internationally successful runners originate from a small tribe that accounts for approximately 3% of the total Kenyan population also points to a possible genetic component. Whether this is subject to influence from other co-factors, such as altitude or training effects acquired during childhood, remains as yet unresolved.